Improving German Speaking through YouTube Media in Higher Education - Mannahali, Misnah; Angreany, Femmy; Rosmaladewi, Rosmaladewi (Universitas Negeri Makassar, 2024)
This study aims to obtain data and information about the effectiveness and practicality of YouTube in learning German speaking for second-semester students of the German language education study program in terms of learning outcomes and student responses. This study was experimental research, and the experimental model used was a pre-experimental design. The design form used is a one-group pre-test post-test group. The sample selection was done using the purposive sampling technique. Data collection was done through a German-speaking skill test. The data were analyzed using t-test analysis. The findings of the research revealed that there was a significant difference before and after using YouTube media in learning German speaking, and student responses showed very positive results of 87.28%, so it was declared successful, effective, and practical to use in learning German speaking.